Partnering to change the world for people with haemophilia: 6th Haemophilia Global Summit, Prague, Czech Republic, 24–26th September 2015. (13th June 2016) - Astermark, Jan; Hart, Dan; Lobet, Sébastien; Blatný, Jan; d'Oiron, Roseline; Kenet, Gili; Dolan, Gerry; Libotte, Valérie; Hermans, Cedric
Abstract: The 6 th Haemophilia Global Summit was held in Prague, Czech Republic, in September 2015. The programme was designed by an independent Scientific Steering Committee of haemophilia experts and aimed to share optimal management strategies for haemophilia at all life stages, explore recent potential advances in the management of haemophilia A and B and discuss challenges in haemophilia care. In this supplement from the meeting, Dan Hart reviews the lessons that can be learnt from cost‐constrained environments with regard to improving care for people with haemophilia globally. Sébastien Lobet discusses the importance of physical activity for optimising care and Roseline d'Oiron and Jan Blatný consider the role of real‐world data in understanding the effect of treatment in a clinical setting over the long term and the true impact of treatment on the day‐to‐day life of the patient. Gili Kenet addresses the current challenges relating to the optimal management of prophylaxis, and Gerry Dolan and Cedric Hermans discuss the value of pharmacokinetic (PK) parameters in informing treatment decisions. Cedric Hermans and Valérie Libotte explore the importance of considering social and occupational development factors as an integral part of haemophilia care, and Jan Astermark reviews key strategies to predict and prevent inhibitor development.